Is the United Kingdom Becoming a Federal State? - Lemire, Samuel (Trinity College Dublin. School of Law. Discipline of Law, 2022)
This thesis investigates whether the devolution processes that were triggered at the turn of the millennium have turned the United Kingdom into a federal state. Based on an analysis of the Welsh, Scottish, and Northern Irish devolution processes post-1998, I argue that the United Kingdom has now become a federal state in substance, if not in form. Traditional theoretical accounts have consistently posited that a formal written constitution is necessary to uphold and entrench federal principles. Accordingly, doubts have been raised that these principles could be transplanted and implemented in a polity that does not have a canonical codified constitution. However, I contend that British constitutional law, due to its dual and flexible nature, guarantees the supremacy of substantively fundamental principles, such as those characterising federalism. To make this argument, I evaluate whether non-formal common law and conventional devices can make political and legal actors and institutions abide by federal principles, particularly when they implement the substance of the devolution arrangements. I find out that federal principles are implemented substantively, albeit not formally, in the United Kingdom. The structure of this thesis is threefold. First, I examine the substance of its core concepts (federalism, British constitutionalism, and devolution). I observe that the multinational nature of a polity like the United Kingdom can be recognised and constitutionalised through the division of sovereignty. Second, I probe the apparent contradiction between the composite character of the British state and its unitary constitutional essence, which has long been shaped by parliamentary supremacy. I highlight that while the devolution arrangements have empowered the British constituent nations to make normative decisions autonomously, they are formally frail since their implementation overly depends on the will of central institutions. Nevertheless, since the devolution arrangements are substantively robust and authoritative, I ultimately demonstrate that the British constitution upholds, and even entrenches, federal principles in a manner that divides the exercise of British sovereignty concretely and pragmatically.
APPROVED
Keywords: Constitution; Federalism; Devolution; British Constitutionalism; Common Law; Nationalism; Constitutionalism